(Nano)biotechnological approaches in the treatment of cervical cancer: integration of engineering and biology - Xie, Weimin; Xu, Zhengmei (Frontiers in Immunology, 2024)
Cervical cancer is one of the most malignant gynaecological tumors characterised with the aggressive behaviour of the tumor cells. In spite of the development of different strategies for the treatment of cervical cancer, the tumor cells have developed resistance to conventional therapeutics. On the other hand, nanoparticles have been recently applied for the treatment of human cancers through delivery of drugs and facilitate tumor suppression. The stimulisensitive nanostructures can improve the release of therapeutics at the tumor site. In the present review, the nanostructures for the treatment of cervical cancer are discussed.Nanostructures can deliver both chemotherapy drugs and natural compounds to increase anticancer activity and prevent drug resistance in cervical tumor. Moreover, the genetic tools such as siRNA can be delivered by nanoparticles to enhance their accumulation at tumor site.In order to enhance selectivity, the stimuli-responsive nanoparticles such as pH-and redoxresponsive nanocarriers have been developed to suppress cervical tumor. Moreover, nanoparticles can induce photo-thermal and photodynamic therapy to accelerate cell death in cervical tumor. In addition, nanobiotechnology demonstrates tremendous potential in the treatment of cervical cancer, especially in the context of tumor immunotherapy. Overall, metal-, carbon-, lipid-and polymer-based nanostructures have been utilized in cervical cancer therapy. Finally, hydrogels have been developed as novel kinds of carriers to encapsulate therapeutics and improve anti-cancer activity.